Intracorneal injection of a detachable hybrid microneedle for sustained drug delivery. (15th October 2018) - Lee, KangJu; Song, Hyun Beom; Cho, Wonwoo; Kim, Jin Hyoung; Kim, Jeong Hun; Ryu, WonHyoung
Graphical abstract: Abstract: There are increasing demands for long-term and controlled corneal drug delivery to treat various ocular diseases. Although biodegradable ocular inserts or contact lenses have been developed, the invasiveness and inefficiency of the approaches still need to be improved. Microneedle (MN) technology can deliver therapeutic molecules to the eye in a minimally invasive manner. However, the current ocular MN technology is limited to either short-term corneal drug delivery or retinal drug delivery by suprachoroidal injection. For long-term and minimally invasive corneal drug delivery, we have developed a detachable biodegradable MN that can be delivered to the inside of the cornea for sustained drug release. The detachable and biodegradable MN is a hybrid MN consisting of a drug-loaded biodegradable tip and a supporting base. The hybrid MN can be applied to the cornea by impact insertion, and it leaves only the drug-loaded biodegradable tip within the corneal tissue so that it can release the drug for a certain period. By concentration-controlled molding, the dimension of drug-loaded MN tips was precisely controlled and their detachability was optimized. The detachable tip and a supporting base were assembled to form a hybrid MN by pressure-assisted transfer molding. We carefully optimized the dimension of the drug-tip, injection dwell time, and insertion depth to achieve effective intracorneal injection of the drug-tip. The detachable hybrid MN was applied to an Acanthamoeba keratitis model wherein a biodegradable drug-tip was successfully delivered to the inside of the mouse cornea in vivo. Follow-up of the MN-treated cases for 7 days confirmed the therapeutic efficacy of the detachable biodegradable MN tips. Statement of Significance: For the treatment of infectious diseases in the cornea, such as keratitis, eye drops need to be applied topically every hour for a couple of days. This is extremely uncomfortable, and poor compliance to such tightly scheduled drug administration can result in permanent scar formation in the cornea. In this work, we demonstrate a simple and rapid injection of biodegradable microneedle tips in the corneal tissue wherein the tips can deliver antibacterial drugs for 4 days to treat keratitis. Unlike other patch-style microneedle technologies, this approach allows for insertion depth-controlled and highly localized injection of detachable individual microneedle tips to the diseased tissue for sustained drug delivery. This overcomes the limitations of patch-style microneedles such as short-term drug delivery and unnecessary blockage of tissue.